Examining the impact of visa restrictions on international tourist flows using panel data - Artal-Tur, Andrés; Pallardó-López, Vicente J.; Requena-Silvente, Francisco (Estudios de Economía, 2016)
Using newly panel data on visa restrictions for the years 2000 and 2010 in a theory-grounded gravity model, we find a robust, causal negative impact of visa restrictions on international tourist flows. By destination, the detrimental impact of this type of barrier is observed for tourists going to developing countries (with the exception of East and South Asia), but not for those to developed ones. By country of origin of tourists, the impact of visa restrictions appears to be the same for tourists coming from developed and developing countries. These findings have important consequences in policy terms for tourism management at a regional level.